Correlation of Serum Low Density Lipoprotein Cholesterol and High Density Lipoprotein Cholesterol with Type 2 Diabetes Mellitus - Yeasmin, Nahid; Akhter, Qazi Shamima; Mahmuda, Sayeeda; Yeasmin, Sultana; Afroz, Rumana; Hasan, Mahmudul; Rabbani, Rukhshana; Akhter, Shamima; Chowdhury, Md Ashif Mashud; Dhar, Uma (Journal of Dhaka Medical College, 2018)
Background: Diabetes mellitus is one of the most widespread endocrine disorders in female and its complications are increasing all over the world, leading to life threatening medical problems like cardiovascular diseases, stroke and end stage renal diseases. A correlation between hyperlipidemia and type 2 diabetes mellitus has been identified. The study was carried out to observe the correlation of serum low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C) level with type 2 diabetes mellitus in adult female subjects. Method: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2011 to December 2011. Total sixty female subjects were selected with age ranging from 30 to 50 years. Among them 30 female subjects with diabetes mellitus were included from out-patient department of Endocrinology, Dhaka Medical College Hospital, Dhaka as study group (B) and 30 apparently healthy females were taken as control group (A) for comparison. Estimation of serum fasting serum LDL-C and HDL-C levels was done by enzymatic method in the department of Physiology, Dhaka Medical College Dhaka in both groups. Fasting serum insulin level was measured by ELISA method in the laboratory of National Institute of ENT, Dhaka and fasting blood glucose was estimated by glucose oxidase method in the department of Physiology, Dhaka Medical College in both groups. Data were analyzed by Unpaired Student’s- test and Pearson’s correlation co-efficient (r) test as applicable. Results: The value of fasting serum LDL-C level was significantly higher in study subjects than those of control. Again, fasting serum HDL-C level was significantly lower in study subjects in comparison to controls. In study subjects fasting serum LDL showed positive correlation and fasting serum HDL-C levels showed negative correlation with fasting blood glucose and serum insulin level. Conclusion: Present study reveals that serum insulin and blood glucose level have positive relationship with low density lipoprotein cholesterol (LDL-C) and negative relationship with high density lipoprotein cholesterol (HDL-C) levels. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 140-147